PP-006 Extemporaneously compounded oral medicines in Spanish hospital pharmacies. (24th February 2014) - Carvalho, M; Taylor, K; Tuleu, C
Abstract : Background: Pharmaceutical compounding, the preparation of customised medicines in order to meet the specific needs of patients, is an invaluable therapeutic alternative that allows patients the benefit of a bespoke treatment. Although an age-old practice, little is known regarding current compounding practices in Spain. Purpose: To understand the current compounding practices in Spain, as follows: Identification of the concept of compounded medicines, legal requirements, professional organisations and information sources on compounding. Identification and characterisation of the oral compounded medicines most frequently dispensed in the hospital pharmacy setting. Materials and methods: A self-completion questionnaire was developed and distributed to a selected sample of 40 hospitals across the country, including general hospitals, university hospitals and paediatric-specialist hospitals. These hospitals were identified as the ones in which the largest quantities of compounded medicines were likely to be dispensed in Spain. Results: A response rate of 78% was obtained and a total of 281 different active substances (including 9 Narrow Therapeutic Index (NTI) drugs) was reported by the participant hospital pharmacies. The top 3 therapeutic groups were cardiovascular drugs, nutritional agents and antibacterials. Oral solid dosage forms were reported by 93% of participant hospitals and included (in decreasing order) capsules, oral powders and powders for oral liquids, in a total of 1, 052, 518 individual units. Oral liquid dosage forms were reported by 90% of participant hospitals and included (in decreasing order) solutions, suspensions, syrups, tinctures, oral drops and elixirs (multidose) and oral syringes (unidose), in a total sum of 60, 117 multidose and 59, 142 unidose containers. The top 5 active substances dispensed as oral liquids were: omeprazole, methadone HCl, colistin sulfate, amphotericin B and ranitidine. Conclusions: Pharmaceutical compounding is a common practice in hospital pharmacies across Spain. There are several professional organisations and information sources on compounding and there is a detailed legal framework that regulates this practice. A wide variety of compounded medicines was dispensed in the hospital setting. Oral liquid dosage forms were more frequently dispensed than oral solids. No conflict of interest.